FACTORS AFFECTING MENTAL HEALTH IN PREGNANT AND BREASTFEEDING WOMEN - Adisti, Lutfi; Wulandari, Aulia; Tunggal Mutika, Winnie (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Mental health in pregnant and breastfeeding women causes anxiety, stress, insomnia, baby blues, and depression if not handled properly. Pregnant women who have mental disorders can increase the risk to the fetus in the form of poor fetal development, premature birth, and LBW. Objective : To identify risk factors that affect mental health in pregnant and breastfeeding women. Research Methods/ Implementation Methods : A literature review using four databases, namely Elsevier, Pubmed, Google Scholar, and Garuda using the keywords “mental health”, “depression”, “pregnant women”, “breastfeeding mothers”, and “related factors”. Results : Twenty journals have eleven significant journals with age, six significant journals with education, eight significant journals with social support, eight significant journals with parity, two significant journals with knowledge, six significant journals with exercise and physical activity, four significant journals with income, six significant journals with employment, four significant journals with anxiety, towards mental health in pregnant and breastfeeding mothers. Conclusion/Lesson Learned : Age, parity, education, knowledge, income, physical activity, type of labor, and social support are important in maintaining the mental health of pregnant and lactating women. Structured interventions that involve the family can be an effective preventive effort to reduce mental stress and improve maternal readiness for pregnancy and childbirth.